How to improve sustainability: the critical role of education for Syrian refugees. Issue 5 (4th July 2019) - Albakri, Tareq Z.; Shibli, Rabih
ABSTRACT: The Middle East region has witnessed tumultuous humanitarian crises over the past decade resulting from political conflict and forced migration of refugees fleeing for safety. Fulfilling Sustainable Development Goal 4 within the context of protracted conflict and large-scale forced migration has been very challenging to host countries and concerned civil society organisations. The Syrian conflict has generated 5.6 million registered refugees in Lebanon, Turkey, Jordan, Iraq, and Egypt. This viewpoint highlights the critical role of education in relation to SDG4, sharing the Ghata schools project as a case study, which was designed with a view to sustainability and equitable opportunity for Syrian refugees in Lebanon. Key lessons from this five-year project are shared, offering considerations to broader efforts towards sustainable quality education for refugees.